Magnetic measurements in the stratosphere and their role in the studies of magnetic field of the Earth - Yu. P. Tsvetkov; S. V. Filippov; V. V. Ivanov; O. M. Brekhov (Геофизический журнал, 2016)
Listed non-exhaustive list of tasks stratospheric magnetic surveys, at which decision the use of gradient measurements of the geomagnetic field on board a stratospheric balloon increases the accuracy of the research field of nature. An example use of such measurements, made in 2013 during the flight of the balloon over the territory of Central Russia, to identify the lithospheric magnetic field of the Earth is demonstrated. The advantage of this research tool in comparison with terrestrial and satellite surveys for the some tasks is shown. To improve the models of the anomalous magnetic field in near-earth space and the researches of the deep structure, magnetic properties and parameters the earth's crust it is necessary to use the data of the geomagnetic gradient surveys at the balloon altitudes (20—40 km).